Answer:
Simplifying
(4x + -6) = (x + 6y)
Reorder the terms:
(-6 + 4x) = (x + 6y)
Remove parenthesis around (-6 + 4x)
-6 + 4x = (x + 6y)
Remove parenthesis around (x + 6y)
-6 + 4x = x + 6y
Solving
-6 + 4x = x + 6y
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-1x' to each side of the equation.
-6 + 4x + -1x = x + -1x + 6y
Combine like terms: 4x + -1x = 3x
-6 + 3x = x + -1x + 6y
Combine like terms: x + -1x = 0
-6 + 3x = 0 + 6y
-6 + 3x = 6y
Add '6' to each side of the equation.
-6 + 6 + 3x = 6 + 6y
Combine like terms: -6 + 6 = 0
0 + 3x = 6 + 6y
3x = 6 + 6y
Divide each side by '3'.
x = 2 + 2y
Simplifying
x = 2 + 2y